Uniform Sb2S3 optical coatings by chemical spray method - Eensalu, Jako S.; Katerski, Atanas; Kärber, Erki; Oja Acik, Ilona; Mere, Arvo; Krunks, Malle (Beilstein Journal of Nanotechnology, 2019)
Antimony sulfide (Sb2S3), an environmentally benign material, has been prepared by various deposition methods for use as a solar absorber due to its direct band gap of ≈1.7 eV and high absorption coefficient in the visible light spectrum (1.8 × 105 cm−1 at 450 nm). Rapid, scalable, economically viable and controllable in-air growth of continuous, uniform, polycrystalline Sb2S3 absorber layers has not yet been accomplished. This could be achieved with chemical spray pyrolysis, a robust chemical method for deposition of thin films. We applied a two-stage process to produce continuous Sb2S3 optical coatings with uniform thickness. First, amorphous Sb2S3 layers, likely forming by 3D Volmer–Weber island growth through a molten phase reaction between SbCl3 and SC(NH2)2, were deposited in air on a glass/ITO/TiO2 substrate by ultrasonic spraying of methanolic Sb/S 1:3 molar ratio solution at 200–210 °C. Second, we produced polycrystalline uniform films of Sb2S3 (Eg 1.8 eV) with a post-deposition thermal treatment of amorphous Sb2S3 layers in vacuum at 170 °C, <4 × 10−6 Torr for 5 minutes. The effects of the deposition temperature, the precursor molar ratio and the thermal treatment temperature on the Sb2S3 layers were investigated using Raman spectroscopy, X-ray diffraction, scanning electron microscopy, energy dispersive X-ray spectroscopy and UV–vis–NIR spectroscopy. We demonstrated that Sb2S3 optical coatings with controllable structure, morphology and optical properties can be deposited by ultrasonic spray pyrolysis in air by tuning of the deposition temperature, the Sb/S precursor molar ratio in the spray solution, and the post-deposition treatment temperature.
Keywords: antimony sulfide; thin films; ultrasonic spray; vacuum annealing; Volmer–Weber growth

(untitled) - Versavel, M. Y.; Haber, J. A. (Thin Solid Films, 2007)

(untitled) - Messina, S.; Nair, M. T. S.; Nair, P. K. (Thin Solid Films, 2007)

(untitled) - Itzhaik, Y.; Niitsoo, O.; Page, M.; Hodes, G. (J. Phys. Chem. C, 2009)

(untitled) - Choi, Y. C.; Lee, D. U.; Noh, J. H.; Kim, E. K.; Seok, S. I. (Adv. Funct. Mater., 2014)

(untitled) - Choi, Y. C.; Seok, S. I. (Adv. Funct. Mater., 2015)

(untitled) - Wedemeyer, H.; Michels, J.; Chmielowski, R.; Bourdais, S.; Muto, T.; Sugiura, M.; Dennler, G.; Bachmann, J. (Energy Environ. Sci., 2013)

(untitled) - Parize, R.; Katerski, A.; Gromyko, I.; Rapenne, L.; Roussel, H.; Kärber, E.; Appert, E.; Krunks, M.; Consonni, V. (J. Phys. Chem. C, 2017)

(untitled) - Sung, S.-J.; Gil, E. K.; Lee, S.-J.; Choi, Y. C.; Yang, K.-J.; Kang, J.-K.; Cho, K. Y.; Kim, D.-H. (J. Ind. Eng. Chem. (Amsterdam, Neth.), 2017)

(untitled) - Patil, P. S. (Mater. Chem. Phys., 1999)

(untitled) - Kriisa, M.; Krunks, M.; Oja Acik, I.; Kärber, E.; Mikli, V. (Mater. Sci. Semicond. Process., 2015)

(untitled) - Rajpure, K. Y.; Bhosale, C. H. (Mater. Chem. Phys., 2002)

(untitled) - Kärber, E.; Katerski, A.; Oja Acik, I.; Mere, A.; Mikli, V.; Krunks, M. (Beilstein J. Nanotechnol., 2016)

(untitled) - Kim, D.-H.; Lee, S.-J.; Park, M. S.; Kang, J.-K.; Heo, J. H.; Im, S. H.; Sung, S.-J. (Nanoscale, 2014)

(untitled) - Madarász, J.; Pokol, G. (J. Therm. Anal. Calorim., 2007)

(untitled) - Timchenko, V. P.; Novozhilov, A. L.; Slepysheva, O. A. (Russ. J. Gen. Chem., 2004)

(untitled) - Parize, R.; Cossuet, T.; Chaix-Pluchery, O.; Roussel, H.; Appert, E.; Consonni, V. (Mater. Des., 2017)

(untitled) - Chang, H.; Huang, P. J. (J. Raman Spectrosc., 1998)

(untitled) - Liu, Y.; Eddie Chua, K. T.; Sum, T. C.; Gan, C. K. (Phys. Chem. Chem. Phys., 2014)

(untitled) - Makreski, P.; Petruševski, G.; Ugarković, S.; Jovanovski, G. (Vib. Spectrosc., 2013)

(untitled) - Ibáñez, J.; Sans, J. A.; Popescu, C.; López-Vidrier, J.; Elvira-Betanzos, J. J.; Cuenca-Gotor, V. P.; Gomis, O.; Manjón, F. J.; Rodríguez-Hernández, P.; Muñoz, A. (J. Phys. Chem. C, 2016)

(untitled) - Kharbish, S.; Libowitzky, E.; Beran, A. (Eur. J. Mineral., 2009)

(untitled) - Medles, M.; Benramdane, N.; Bouzidi, A.; Sahraoui, K.; Miloua, R.; Desfeux, R.; Mathieu, C. (J. Optoelectron. Adv. Mater., 2014)
https://joam.inoe.ro/index.php?option=magazine&op=view&idu=3498&catid=84

Infrared and Raman Spectra of Inorganic and Coordination Compounds - Nakamoto, K. (Wiley-Blackwell, 2008)

(untitled) - Hofmann, W. (Z. Kristallogr., 1933)

(untitled) - Petzelt, J.; Grigas, J. (Ferroelectrics, 1973)

(untitled) - Grovenor, C. R. M. (J. Phys. C: Solid State Phys., 1985)

(untitled) - Escorcia-García, J.; Becerra, D.; Nair, M. T. S.; Nair, P. K. (Thin Solid Films, 2014)

(untitled) - Boughalmi, R.; Boukhachem, A.; Kahlaoui, M.; Maghraoui, H.; Amlouk, M. (Mater. Sci. Semicond. Process., 2014)

(untitled) - Birkholz, M.; Selle, B.; Fuhs, W.; Christiansen, S.; Strunk, H. P.; Reich, R. (Phys. Rev. B, 2001)

Chemistry of the Elements - Greenwood, N. N.; Earnshaw, A. (Butterworth-Heinemann, 1997)

(untitled) - Fujishima, A.; Zhang, X.; Tryk, D. A. (Surf. Sci. Rep., 2008)

(untitled) - Madarász, J.; Krunks, M.; Niinistö, L.; Pokol, G. (J. Therm. Anal. Calorim., 2015)

(untitled) - Madarász, J.; Krunks, M.; Niinistö, L.; Pokol, G. (J. Therm. Anal. Calorim., 2004)

(untitled) - Polivtseva, S.; Oja Acik, I.; Krunks, M.; Tõnsuaadu, K.; Mere, A. (J. Therm. Anal. Calorim., 2015)

(untitled) - Lan, C.; Liang, G.; Lan, H.; Peng, H.; Su, Z.; Zhang, D.; Sun, H.; Luo, J.; Fan, P. (Phys. Status Solidi RRL, 2018)

(untitled) - Zheng, Y. C.; Yang, S.; Chen, X.; Chen, Y.; Hou, Y.; Yang, H. G. (Chem. Mater., 2015)

(untitled) - Kushkhov, A. R.; Gaev, D. S.; Rabinovich, O. I.; Stolyarov, A. G. (Crystallogr. Rep., 2013)

(untitled) - Piacente, V.; Scardala, P.; Ferro, D. (J. Alloys Compd., 1992)

CRC Handbook of Chemistry and Physics - Lide, D. R. (CRC Press, 2006)

(untitled) - Ozturk, I. I.; Kourkoumelis, N.; Hadjikakou, S. K.; Manos, M. J.; Tasiopoulos, A. J.; Butler, I. S.; Balzarini, J.; Hadjiliadis, N. (J. Coord. Chem., 2011)

(untitled) - Rohrer, G. S. (Metall. Mater. Trans. A, 2010)

(untitled) - Volmer, M.; Weber, A. (Z. Phys. Chem., Stoechiom. Verwandtschaftsl., 1926)

(untitled) - Abraham, D. B.; Newman, C. M. (EPL, 2009)

The Principles of Inorganic Chemistry - Ostwald, W. (Macmillan and Co., Ltd., 1904)

(untitled) - Brookins, D. G. (Econ. Geol., 1972)

ASM Handbook, Fundamentals of Modeling for Metals Processing - Clouet, E. (Modeling of Nucleation Processes, 2009)

(untitled) - Lokhande, C. D.; Sankapal, B. R.; Mane, R. S.; Pathan, H. M.; Muller, M.; Giersig, M.; Ganesan, V. (Appl. Surf. Sci., 2002)

(untitled) - Krishnan, B.; Arato, A.; Cardenas, E.; Roy, T. K. D.; Castillo, G. A. (Appl. Surf. Sci., 2008)

(untitled) - Zhu, G.; Huang, X.; Hojamberdiev, M.; Liu, P.; Liu, Y.; Tan, G.; Zhou, J.-p. (J. Mater. Sci., 2011)

(untitled) - Bessegato, G. G.; Cardoso, J. C.; Silva, B. F. d.; Zanoni, M. V. B. (J. Photochem. Photobiol., A, 2014)

(untitled) - Zheng, L.; Jiang, K.; Huang, J.; Zhang, Y.; Bao, B.; Zhou, X.; Wang, H.; Guan, B.; Yang, L. M.; Song, Y. (J. Mater. Chem. A, 2017)

(untitled) - Wang, W.; Strössner, F.; Zimmermann, E.; Schmidt-Mende, L. (Sol. Energy Mater. Sol. Cells, 2017)

(untitled) - Kozytskiy, A. V.; Stroyuk, O. L.; Skoryk, M. A.; Dzhagan, V. M.; Kuchmiy, S. Y.; Zahn, D. R. T. (J. Photochem. Photobiol., A, 2015)

(untitled) - Kamruzzaman, M.; Chaoping, L.; Yishu, F.; Farid Ul Islam, A. K. M.; Zapien, J. A. (RSC Adv., 2016)

(untitled) - Morteani, G.; Ruggieri, G.; Möller, P.; Preinfalk, C. (Miner. Deposita, 2011)

(untitled) - Oja Acik, I.; Junolainen, A.; Mikli, V.; Danilson, M.; Krunks, M. (Appl. Surf. Sci., 2009)

(untitled) - Tauc, J.; Grigorovici, R.; Vancu, A. (Phys. Status Solidi, 1966)

(untitled) - Grozdanov, I. (Semicond. Sci. Technol., 1994)

(untitled) - Grozdanov, I.; Ristov, M.; Sinadinovski, G.; Mitreski, M. (J. Non-Cryst. Solids, 1994)

(untitled) - Medina-Montes, M. I.; Montiel-González, Z.; Paraguay-Delgado, F.; Mathews, N. R.; Mathew, X. (J. Mater. Sci.: Mater. Electron., 2016)

(untitled) - Wojdyr, M. (J. Appl. Crystallogr., 2010)